2019
DOI: 10.1002/ece3.5108
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall seasonality predicts the germination behavior of a tropical dry‐forest vine

Abstract: Seed dormancy is considered to be an adaptive strategy in seasonal and/or unpredictable environments because it prevents germination during climatically favorable periods that are too short for seedling establishment. Tropical dry forests are seasonal environments where seed dormancy may play an important role in plant resilience and resistance to changing precipitation patterns. We studied the germination behavior of seeds from six populations of the Neotropical vine Dalechampia scandens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
(87 reference statements)
0
14
0
Order By: Relevance
“…Assuming that seasonality in precipitation is an important source of selection on seed dormancy and germination behaviour, the weak tendency for seed size to increase with seasonality tends to support the conclusion that seed size in D. scandens is correlated with dormancy and germination behaviour (Martins et al, 2019). However, even taken at face value, this effect remains limited, with an increase in seed size of ca.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Assuming that seasonality in precipitation is an important source of selection on seed dormancy and germination behaviour, the weak tendency for seed size to increase with seasonality tends to support the conclusion that seed size in D. scandens is correlated with dormancy and germination behaviour (Martins et al, 2019). However, even taken at face value, this effect remains limited, with an increase in seed size of ca.…”
Section: Discussionmentioning
confidence: 94%
“…Previous experiments have shown that neither seed size nor within-blossom variation in seed size is detectably affected by the number of fathers siring the clutch (Pélabon et al, 2015). Furthermore, within populations, seed size correlates positively with the duration of seed after-ripening required before germination, and among populations, the duration of the after-ripening period correlates positively with environmental seasonality (Martins et al, 2019). Once dormancy is broken, however, larger seeds have a higher probability of germinating (Pélabon et al, 2005).…”
Section: Study Organismsmentioning
confidence: 87%
See 3 more Smart Citations